2017
DOI: 10.17135/jdhs.2017.17.5.433
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid-Induced TWIST1 and Slug Expression in Oral Cancer Cell Invasion

Kyung Hwa Cho

Abstract: Relative to its incidence, oral cancer has serious negative social effects. The exact causes of oral cancer have not been clarified, but many studies have implicated smoking and drinking. However, the fundamental mechanism of oral cancer causation has yet to be elucidated. Lysophosphatidic acid (LPA) augments epithelial mesenchymal transition (EMT) and development of various cancer cells. However, a detailed mechanistic explanation for LPA-induced EMT and the effects of EMT-promoting conditions on oral squamou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Recently, our group reported that LPA plays an important role in promoting the metastasis of oral cancer cells by upregulating the expression levels of TWIST1 and Slug 12,13) . However, the exact mechanism by which LPA induces oral cancer metastasis remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group reported that LPA plays an important role in promoting the metastasis of oral cancer cells by upregulating the expression levels of TWIST1 and Slug 12,13) . However, the exact mechanism by which LPA induces oral cancer metastasis remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%